3D Microstructured Scaffolds to Support Photoreceptor Polarization and Maturation. Issue 39 (14th August 2018) - Jung, Yei Hwan; Phillips, M. Joseph; Lee, Juhwan; Xie, Ruosen; Ludwig, Allison L.; Chen, Guojun; Zheng, Qifeng; Kim, Tong June; Zhang, Huilong; Barney, Patrick; Min, Jee; Barlow, Katherine; et al.
Abstract: Blinding disorders of the outer retina involve dysfunction and degeneration of photoreceptors. One potential approach to treat these forms of blindness is to repopulate the outer retina via a simple bolus injection of donor photoreceptors. However, this may not be ideal due to the highly polarized organization of photoreceptors that include apical light sensing photopigments and basal axon terminals. Furthermore, bolus injections create uncertainty with regard to the area, density, and retention of donor cells. Here, a novel and robust microfabrication process is developed to create 3D, micrometer‐sized complex structures in ultrathin and biocompatible elastomer films (nonbiodegradable polydimethylsiloxane and biodegradable poly(glycerol‐sebacate)) that can serve as polarizable photoreceptor delivery scaffolds, consisting of an array of cup‐shaped photoreceptor capture wells that funnel into a microchannel. This "wine glass" scaffold design promotes efficient capture of human pluripotent stem‐cell‐derived photoreceptor cell bodies and guidance of basal axon extensions, ultimately achieving a uniform level of organization and polarization that is not possible with bolus injections or previously described scaffolds. In addition to future therapeutic applications, our scaffold design and materials provide a platform to generate reproducible and scalable in vitro models of photoreceptor‐based diseases. Abstract : 3D microstructured thin‐film biodegradable elastomer scaffolds designed to capture and guide human stem‐cell‐derived photoreceptors are engineered by employing microfabrication and micromolding techniques. This scaffold promotes the polarization of a high density of photoreceptors and is well‐suited for future therapeutic and disease modeling applications.